A STUDY OF MATHEMATICAL METHODS FOR METROLOGICAL EVALUATION OF TECHNICALLY COMPLEX (KNOWLEDGE-BASED) TEST SYSTEM OF DESIGN - Fedorov, V. O. (Science and Transport Progress, 2006)
The results of research of methods of metrology estimation of the difficult technical tester systems are described in the article